ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DALAM RANGKA EFEKTIVITAS PENGENDALIAN INTERNAL PERUSAHAAN PADA PT ETHICA INDUSTRI FARMASI - Fahira, Bella (Jurnal Ilmiah Wahana Pendidikan, 2024)
Payroll accounting information system is needed in the company system to help make decisions and implementation of employee payroll. This study aims to find out how the application of how to apply payroll accounting information system at PT. Ethica of the Pharmaceutical Industry. The analytical technique used is a qualitative descriptive analysis technique, namely by describing the existing payroll accounting inromation system in the company which includes the application in the payroll system of related functions, documents used, accounting records used, network of procedures that help stem and the effectiveness of internal control. The data collection method uses interviews and documentation. Based on the results of research conducted showing a payroll accounting information system practiced at PT. Ethica Pharmaceutical Industry is very good and has been in accordance with theory because it has fulfilled an adequate internal control system because it includes all components of internal control. Where each part has carried out its responsibilities properly and is also transparent so that there is no misappropriation.